Bronchopulmonary Sequestration with Morbid Neonatal Pleural Effusion despite Successful Antenatal Treatment - Divjak, Natalie; Vasseur Maurer, Sabine; Giannoni, Eric; Vial, Yvan; de Buys Roessingh, Anthony; Wildhaber, Barbara E. (Frontiers in Pediatrics, 2017)
Introduction: Bronchopulmonary sequestration may cause prenatal pleural effusion (PE) or even hydrops. This case describes a fetus presenting with severe PE, which prenatally waned completely under steroid treatment, yet surprisingly reappeared rapidly after birth, requiring early surgical intervention. Case description: A male fetus was diagnosed with left bronchopulmonary sequestration and severe PE. After 3 courses of prenatal steroid therapy for each recurrence of PE from 27 weeks of gestation we observed a complete regression of PE prenatally. Yet, PE recurred 18 hours after birth and persisted after repeated drainages and steroid therapy. Early total resection of the extra-lobar bronchopulmonary sequestration was performed and led to complete recovery without recurrence of PE. Conclusion: This report underlines that in cases of bronchopulmonary sequestration presenting with prenatal PE needing fetal intervention, even if full regression of PE is observed before birth, there might be a need for surgical excision during the neonatal period.